Soliton solutions to phi-four and strain wave equation through the exp -expansion method - Chowdhury, Md. Sazzad Hossien; Akbar, M. Ali; Hosen, Md. Alal (Estacao Vitivinicola Nacional Dios Portos, 2015)
The exp(−F(h )) -expansion method is direct, concise and simple to carry out compared to other existing methods. In this article, we implement the exp(−F(h )) -expansion method through the nonlinear Phi-four equation, an instructive model arising in particle physics and the strain wave equation in microstructured solids to construct the exact periodic solutions and soliton solutions. The solutions are expressed in terms of the hyperbolic functions, the trigonometric functions, the exponential functions and the rational functions. The obtained results show that the exp(−F(h )) - expansion method is easy and provide powerful mathematical tool for solving nonlinear evolution equations in mathematical physics and engineering.